Charles Taylor - Abbey, Ruth 1961- (Contemporary philosophy in focus, 2004)
Charles Taylor is beyond question one of the most distinctive figures in the landscape of contemporary philosophy. In a time of increasing specialization Taylor's ability to contribute to philosophical conversations across a wide spectrum of ideas is distinctive and impressive. These areas include moral theory, theories of subjectivity, political theory, epistemology, hermeneutics, philosophy of mind, philosophy of language and aesthetics. His most recent writings have seen him branching into the study of religion. Written by a team of international authorities, this collection will be read primarily by students and professionals in philosophy, political science and religious studies, but will appeal to a broad swathe of professionals across the humanities and social sciences